Updating the theoretical aspects and practical background of work stress and its assessment in teachers - Calderón Landívar, Ruth; Carrera Macías, María Angeline; Calazacón Aguavil, Erika Mariela; Chávez-Arizala, Jenrry Fredy (Salud Integral y Comunitaria, 2025)
Introduction: Work stress is described as a series of physical and psychological reactions that occur when workers must cope with occupational demands.Objective: to update the state of the art of the theoretical aspects and practical background of work stress and its assessment in teachersMethod: a narrative review of the updated bibliography was carried out using recognized databases.Development: Stress is a natural reaction to the body; however, constantly remaining under that pressure can severely affect health. Mental stress is defined as that which is produced by anguish, worries in many cases of an economic or emotional nature, problems at work, among others: work stress, anxiety, depression, maladaptive beliefs, demotivation, work pressure, poor coping, etc.Conclusions: The assessment of work stress in teachers is crucial to identify factors that affect their well-being and performance. The theoretical aspects highlight the importance of adequate measurement methods, the relationship between stress and mental health, and the need to implement intervention strategies. Understanding these elements can improve working conditions and educational quality in the teaching field.